Transactions on Intelligent Welding Manufacturing Volume III No. 2 2019 - Chen, Shanben; Zhang, Yuming; Feng, Zhili; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
The primary aim of this volume is to provide researchers and engineers from both academic and industry with up-to-date coverage of new results in the field of robotic welding, intelligent systems and automation. The book is mainly based on papers selected from the 2019 International Workshop on Intelligentized Welding Manufacturing (IWIWM$1 (B2019) in USA. The articles show that the intelligentized welding manufacturing (IWM) is becoming an inevitable trend with the intelligentized robotic welding as the key technology. The volume is divided into four logical parts: Intelligent Techniques for Robotic Welding, Sensing of Arc Welding Processing, Modeling and Intelligent Control of Welding Processing, as well as Intelligent Control and its Applications in Engineering.s
Intelligentized technologies for robotic welding -- Advanced welding robot technologies -- Programming and simulation of welding robots -- Vision guiding and tracking technologies of welding robots -- Quality control of robotic welding -- Tele-control and network technologies for robotic welding -- Sensing technologies for welding process -- Robotic welding under special environment -- Intelligentized and digital welding equipments -- Intelligentized technologies for industrial process.
Keywords: Robotics; Automation; Industrial engineering; Production engineering; Control engineering; Robotics and Automation; Robotics; Industrial and Production Engineering; Control and Systems Theory